26: Coda - The past and future of analytical sociology (Edward Elgar Publishing, 2021)
In this chapter, I reflect on how the field of analytical sociology has developed since the late 1990s. I discuss briefly the birth of analytical sociology, what motivated its emergence, and what its most essential characteristics are. Thereafter, and in more detail, I consider a set of topics that I believe to be of crucial importance for the future of analytical sociology. In particular, I focus on the role of action-based explanations of macro-level change. I argue that analytical sociologists should be less wedded to intentional explanations, and instead focus their efforts on constructing empirically plausible and empirically verifiable models of action and interaction.